Disseminated cryptococcosis and hemochromatosis: clues to diagnosis - Larry Nichols; Lindsey Rowley; Ashley Lall (University of São Paulo, 2021)
Hepatic cirrhosis, diabetes mellitus and iron overload can each independently predispose to cryptococcosis. Hereditary hemochromatosis leads to all three of these predispositions. This report is the case of a patient with chronic hepatitis B virus infection and cirrhosis, who had markedly elevated serum ferritin and 99% transferrin saturation, and developed a leukemoid reaction. Autopsy revealed disseminated cryptococcosis for which the leukemoid reaction was a clue and possible hereditary hemochromatosis of which elevated ferritin and transferrin saturation can be clues. Hereditary hemochromatosis is an important diagnosis clinicians should never miss because early treatment with phlebotomy can be life-saving. Disseminated cryptococcosis can be rapidly diagnosed with serum cryptococcal antigen test and is treatable.